Kunskap, rutiner och samverkan när äldre blir utsatta för våld i nära relationer En kvantitativ studie utifrån biståndshandläggares perspektiv - Lindroth,Anni; Kristiansson,Emma (2026)
Domestic abuse among the elderly is an increasing social problem where research is lacking. The aim of this study was to investigate whether social workers perceive that they possess and receive sufficient knowledge, organizational support, and professional development regarding elder abuse, as well as to explore collaboration with other organizations involved in addressing domestic violence. In this paper, we introduce a quantitative study conducted in Scania, Sweden. The study is focused on social workers’ perspectives on knowledge, organizational routines, and collaboration with other organizations in cases where the elderly are subjected to domestic violence. The study included social workers responsible for casework involving the elderly who require municipal support in managing everyday life. To collect data, we contacted all 33 municipalities in Scania, of which 25 agreed to participate. In total, 115 social workers completed our survey. The analysis was guided by Michael Lipsky’s theory of street-level bureaucracy, which was used to understand how social workers exercise discretion when identifying and responding to domestic abuse among the elderly. Our findings indicate that most social workers feel confident in their knowledge of elder abuse, but many also expressed a desire for additional training and professional development. Perceived confidence was influenced by the presence of organizational routines and opportunities for continued education related to elder abuse. The results highlight significant potential for improvement in collaboration with other organizations and professional groups involved in domestic violence.
Keywords: knowledge; elderly; social worker; domestic abuse; collaboration